Primary Care Support Tools for Digestive Health Care: A Mixed Method Study - Mubashir Arain; Leanne Reeb; Rebecca C. Miyagishima; Julia Carter; Kerri L. Novak (Canadian Journal of Gastroenterology and Hepatology)
Background. To address the increasing demands for gastroenterology specialty care and increasing wait times, centralized access and triage (CAT) systems, telephone support, and clinical care pathways were implemented to streamline referrals and support management of low-risk gastrointestinal (GI) conditions in the primary care medical home. This study aimed to understand primary care providers (PCPs) and GI specialists’ perceptions of these supports, factors that affect support implementation and identify barriers and facilitators for implementing supports from both PCP and GI specialists’ perspectives. Methods. We conducted a mixed method study including surveys and interviews with PCPs and GI specialists. Online surveys and semistructured qualitative interviews were conducted from July 2022 to September 2022. All interviews were transcribed and coded to perform a thematic analysis. Survey data were analyzed in SPSS version 25. Descriptive statistics were employed to summarize and describe the data collected. Inferential statistics were used to identify associations and relationships within the dataset. T-test and chi-square tests were applied at 95% confidence level, with a p value <0.05 (two-sided) considered statistically significant. Results. A total of 36 PCPs responded to the survey. Most respondents were working full-time (73.5%, n = 25) and were female (73.5%, n = 25). Overall, 42% used the pathways regularly, 48% (n = 16) used them occasionally, and very few (9.1%, n = 3) said they were aware but had not used pathways. Overall, PCPs were satisfied with CAT processes and the use of primary care pathways, recognizing the importance of fair and equitable access to specialty care. Specific processes in CAT for vulnerable populations and patients using walk-in clinics were recognized as a limitation, given the lack of ease in completing the required testing and follow-up needed when utilizing the care pathway. Of the 112 GI specialists who received the survey, 28 (25%) completed it, with males (50.0%, n = 14) and females (39.2%, n = 11), remainder no response. Most participate in CAT (73.9%, n = 17) and were remunerated by an alternative relationship plan (ARP) (53.6%, n = 15). Overall, GIs were satisfied with central triaging and primary care pathways, reducing unnecessary time and resource expenditure for referrals. There were statistically significant differences in perceptions among fee for service and alternative relationship plan GI specialists regarding the effectiveness of CAT in improving access and use of health system resources. Conclusion. Overall, PCPs and GI specialists believe utilizing CAT and primary care pathways improves referral quality, reduces resource expenditure, and provides fair and equitable access to GI specialty services. Improvement in CAT processes with improved pathway awareness may reduce unnecessary referrals.